(untitled) (Revista Iberoamericana de Bioética, 2023)
Performing an objective analysis of the exercise of autonomy in a person with a disability can be very complex if one considers beforehand the significant burden of discomfort derived from the limitations endured by the individual, secondary to the very nature of his/her condition, and the external mediators implied. Reviewing theoretical concepts on the possible variables at play in disability decision-making can provide a more accurate view on the difficulty of undertaking a bioethical assessment of the situation, avoiding falling into the trap of prejudice or not giving the appropriate value to the manifestation of the person’s self-will, scenarios with a significant impact on clinical bioethics.